Photochemical efficiency of cashew rootstocks under salt stress and foliar application of potassium silicate - de Fatima, Reynaldo; Nobre, Reginaldo Gomes; Lima, Geovani Soares de; Figueiredo, Francisco Romário Andrade; Souza, Leandro de Pádua; Pimenta, Thiago Alves (Comunicata Scientiae, 2022)
The cashew tree is one of the most economically important fruit trees in Brazil, especially in the Northeast region. However, abiotic factors such as the salinity of water and soils in this region stand out as a limiting factor for this crop, affecting all stages of development, as well as physiological and biochemical processes. Therefore, the use of products that mitigate such damage becomes necessary, with silicon and potassium as a viable alternative. Thus, the objective of this work was to evaluate the photochemical efficiency of cashew tree rootstock subjected to water salinity and foliar potassium silicate application. A randomized block design, distributed in a 5x5 factorial scheme, with four replications and two plants per plot, was used, the treatments being by conductivity of the irrigation water - CEa (0.3, 1, 1.7, 2.4 and 3.1 dS m-1) and potassium silicate concentrations (0, 250, 500, 750 and 1000 mg L-1) applied via the leaves. The salinity of irrigation water causes reductions in the photochemical efficiency of photosystem II and, consequently, in the photosynthetic apparatus of cashew plants, 70 days after sowing. The concentration of 250 mg L-1 of potassium silicate promotes an increase in the quantum yield of cashew plants under salt stress conditions.